Higher Dimensional Charged Black Hole Solutions in f(R) Gravitational Theories - G. G. L. Nashed (Advances in High Energy Physics, 2018)
We present, without any assumption, a class of electric and magnetic flat horizon D-dimension solutions for a specific class of f(R)=R+αR2, all of which behave asymptotically as Anti-de-Sitter spacetime. The most interesting property of these solutions is that the higher dimensions black holes, D>4, always have constant electric and magnetic charges in contrast to what is known in the literature. For D=4, we show that the magnetic field participates in the metric on equal foot as the electric field participates. Another interesting result is the fact that the Cauchy horizon is not identical with the event horizon. We use Komar formula to calculate the conserved quantities. We study the singularities and calculate the Hawking temperature and entropy and show that the first law of thermodynamics is always satisfied.